Increased Gun Violence Among Young Males in Sweden: a Descriptive National Survey and International Comparison - Sturup, Joakim (European journal on criminal policy and research, 2019)
This population-based time-trend study examines gun violence rates among males in Sweden during the years 1996 to 2015 and compares the rate in Sweden to other Western European countries. Data were collected from six registries and are presented descriptively per 100,000 inhabitants. The risks among males in Sweden increased considerably in both lethal and non-lethal gun victimization and perpetration. Among males aged 15 to 29 there was a five-fold increase in risk for victimization in lethal and non-lethal gun violence during the 20-year observation period. In a comparative perspective the rate of gun homicide victimization among males 15 to 29 years was higher in Sweden compared to other Western European countries, while the risk for males over age 30 was at an average level. Based on the results of this study we conclude that gun violence among young males in Sweden has been on the rise and is at a high level compared to other Western European countries. The development of gun violence in Sweden can be characterized as endemic, prevalent in both population and socially vulnerable areas.